BRAVE AND HARDWORKING: A FEMINIST ANALYSIS ON CHILDREN FAIRYTALE “THE LAZY GIRL” - Dewi Purnamasari; Didin Nuruddin Hidayat; Alek Alek (Elite : English and Literature Journal, 2020)
This study analyzed the feminist analysis of children fairytale "The Lazy Girl". In this case, the researchers selected the children fairytale from the perspective of modern feminism framework analysis and identified the moral values of this story. This study focused on the main character of the story drawn as brave and hardworking character. The method used in this study is qualitative descriptive analysis. The researchers analyzed the text of the story from a YouTube channel based on the feminist approach. The finding showed that the second and the third wave of feminist characteristic were used in this story. The main character of this this story showed the brave and hardworking of young girl which related to the feminist framework. In addition, this story has good moral values for children and provides a positive impact for the children.